2021
DOI: 10.3389/feart.2021.648605
|View full text |Cite
|
Sign up to set email alerts
|

Rise of the Colorado Plateau: A Synthesis of Paleoelevation Constraints From the Region and a Path Forward Using Temperature-Based Elevation Proxies

Abstract: The Colorado Plateau’s complex landscape has motivated over a century of debate, key to which is understanding the timing and processes of surface uplift of the greater Colorado Plateau region, and its interactions with erosion, drainage reorganization, and landscape evolution. Here, we evaluate what is known about the surface uplift history from prior paleoelevation estimates from the region by synthesizing and evaluating estimates 1) in context inferred from geologic, geomorphic, and thermochronologic constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Existing paleorelief data from the Arizona transition zone 55 and thermometry-based paleoelevation evidence from the Bidahochi Basin 56 do not require (nor do they rule out) significant post-Miocene uplift. With improvements in the past decade in carbonate clumped isotope thermometry instrumentation and calibrations, as well as the development of model-mediated lapse rates and evaporative fractionation corrections using triple oxygen isotope analysis, higher-resolution paleoaltimetry data 57 paired with the evidence presented here could possibly allow the quantification of uplift attributable to individual lithospheric drips.…”
Section: Discussionmentioning
confidence: 99%
“…Existing paleorelief data from the Arizona transition zone 55 and thermometry-based paleoelevation evidence from the Bidahochi Basin 56 do not require (nor do they rule out) significant post-Miocene uplift. With improvements in the past decade in carbonate clumped isotope thermometry instrumentation and calibrations, as well as the development of model-mediated lapse rates and evaporative fractionation corrections using triple oxygen isotope analysis, higher-resolution paleoaltimetry data 57 paired with the evidence presented here could possibly allow the quantification of uplift attributable to individual lithospheric drips.…”
Section: Discussionmentioning
confidence: 99%
“…27, would also fall along arrays parallel to clay lines (Box 1). Such changes due to elevation on tectonic timescales, however, are also likely to be accompanied by changes in temperature 68 .…”
Section: Seasonality Controls On Clay Fractionation Linesmentioning
confidence: 99%
“…3.2 km respectively, reflect multiple periods of uplift (e.g., Aslan et al 2010;Karlstrom et al, 2012). The underlying causes of uplift are a subject of debate, different hypotheses are summarized by Heitmann et al (2021). To reiterate the review by Heitmann et al (2021), suggested causes of uplift include lower-crustal flow, removal of the Farallon slab during the Laramide orogeny, lithospheric foundering, hydration during the mid-Cenozoic and mantle upwelling, or as an isostatic response from denudation during the late Cenozoic.…”
Section: Geologic History 23mentioning
confidence: 99%
“…The underlying causes of uplift are a subject of debate, different hypotheses are summarized by Heitmann et al (2021). To reiterate the review by Heitmann et al (2021), suggested causes of uplift include lower-crustal flow, removal of the Farallon slab during the Laramide orogeny, lithospheric foundering, hydration during the mid-Cenozoic and mantle upwelling, or as an isostatic response from denudation during the late Cenozoic. The Laramide orogeny occurred during the time frame of approximately 70 Ma to 40 Ma (e.g., Karlstrom et al, 2012), some studies propose that impacts of the Laramide orogeny were exhibited earlier, closer to 100 Ma, west of the Rocky Mountain belt (e.g., Carrapa et al, 2019).…”
Section: Geologic History 23mentioning
confidence: 99%